Membongkar Hubungan Antara Kreativitas Dan Minat Berwirausaha Mahasiswa Papua Di Universitas Nani Bili Nusantara - Reijeng Tabara; La Jejen (Prodi Ekonomi Syariah IAIN Sorong, 2025)
This study aims to examine the influence of creativity on entrepreneurial interest among students at Nani Bili Nusantara University in Sorong, Indonesia. Data were obtained through questionnaires collected from 225 students using a random probability sampling technique. Structural equation modeling (SEM) was used to analyze the data, assessing the direct influence of creativity on entrepreneurial interest. The results show that creativity has a positive and significant effect on entrepreneurial interest. This study contributes to understanding how creativity plays a crucial role in fostering entrepreneurial interest among Papuan students in a cultural context such as Papua. From a practical perspective, these findings suggest that higher education institutions need to develop strategies and programs that focus on enhancing creativity through practical, collaborative, and project-based approaches to foster future entrepreneurial spirit. These insights are particularly useful for similar educational settings seeking to advance entrepreneurial development in resource-rich and culturally diverse regions